Global Smooth Solutions for the Inviscid SQG Equation - Castro, Angel; Córdoba, Diego; Gómez-Serrano, Javier (Memoirs of the American Mathematical Society, 2020)
In this paper, we show the existence of the first non trivial family of classical global solutions of the inviscid surface quasi-geostrophic equation.